Productive consumption: agency, appropriation and value in the creative consuming of David Bowie. Issue 4 (4th July 2017) - Marshall, P. David
Abstract: Productive consumption has been used in economic literature to describe the movement of value to activity that occurs after what we would normally think of as consumption. This essay argues that productive consumption is a useful way to describe the movement of cultural commodities and their proliferation of value beyond consumption by understanding any cultural form is dependent on a co-creation of value by both the artist and the artist's audience/consumers. In the circuit of cultural products, there is something generated that creatively transforms the product in the audience and generates at minimum new structures of value. This article explores the concept of productive consumption in terms of Bowie and his general awareness of this co-creation of value. It identifies the production of value inherent in the consumption process of Bowie through two examples: through Tribute Bands and the way that working performers retool Bowie and his music for a lived experience for a core memorializing Bowie audience; and through the performative persona of Bowie and its play with artifice as opposed to authenticity that became the source for all sorts of performance personas in popular music for more than 40 years.